Nuclear Decommissioning Its History, Development, and Current Status - Laraia, Michele (Lecture Notes in Energy,, 2018)
This book discusses the history of nuclear decommissioning as a science and industry. It explores the early, little-known period when the term "decommissioning" was not used in the nuclear context and the end-of-life operations of a nuclear facility were a low priority. It then describes the subsequent period when decommissioning was recognized as a separate phase of the nuclear lifecycle, before bringing readers up to date with today's state of the art. The author addresses decommissioning as a mature industry in an era in which large, commercial nuclear reactors and other fuel-cycle installations have been fully dismantled, and their sites returned to other uses. The book also looks at the birth, growth and maturity of decommissioning, focusing on how new issues emerged, how these were gradually addressed, and the lessons learned from them. Further, it examines the technologies and management advances in science and industry that followed these solutions. Nuclear Decommissioning is a point of reference for industry researchers and decommissioning practitioners looking to enrich their knowledge of decommissioning in recent decades as well as the modern industry. The book is also of interest to historians and students who wish to learn more about the history of nuclear decommissioning.